Identification of microorganisms associated with sea cucumbers in Johor coastal seawater - Solehin, Siti Najihah; Kamarudin, Kamarul Rahim; Badrulhisham, Nur Sabrina; Mohamed Rehan, Aisyah (Universiti Putra Malaysia, 2024)
Sea cucumbers have been reported to host diverse microorganisms, including pigment-producing microorganisms. Investigating these microorganisms is essential for understanding ecological functions, potential biotechnology applications, and impacts on human health. However, despite their importance, the microbial diversity of sea cucumbers remains largely understudied. Thus, this study aims to identify the microorganisms associated with three species of sea cucumbers: Holothuria pardalis, Holothuria leucospilota, and Holothuria scabra collected from Johor coastal seawater. Identification of these isolates revealed that there were twenty-two strains of bacteria and three strains of fungi in total, representing 11 taxa, including 9 taxa from bacteria, namely Staphylococcus, Bacillus, Brevibacillus, Psychrobacter, Stenotrophomonas, Chryseobacterium, Sphingomonas, and Pseudoxanthomonas, and two taxa from fungi: Aspergillus and Rhodotorula. The isolates were identified using 16S rRNA for bacteria and internal transcribed spacer for fungi. Among these species, Chryseobacterium sp., Sphingomonas sp., and Pseudoxanthomonas sp. were first reported as part of the pigment-producing microorganisms found in sea cucumbers in Malaysia. Thus, these findings offer a novel insight into pigment-producing microorganisms in sea cucumbers and their potential as natural alternatives for colourants.